Efektivitas Pelaksanaan Bimbingan Perkawinan di Kantor Urusan Agama Gedangan Sidoarjo - Nur Lailatul Musyafa’ah; Moch. Luthfir Rahman; Nurul Izzah Yan Bachtiar; Andi Alfarisi; Aprilia Susanti; Lianal Khuluq (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
This article aims to determine the effectiveness of the Marriage Guidance program in KUA, Gedangan District, Sidoarjo. This research is qualitative field research with inductive data analysis. The result of this research is that the implementation of Marriage Guidance at KUA Gedangan Sidoarjo is in line with the Decree of the Director-General of Islamic Community Guidance Number 379 of 2018 concerning Guidelines for the Implementation of Prenuptial Marriage Guidance for Prospective Brides. The program of Marriage Guidance at the KUA, Gedangan District, which has only been implemented for the last two years, has been ineffective because there are several inhibiting factors, including funding, facilities, and infrastructure, and implementation time. After all, the bride and groom cannot attend due to work and the lack of desire for the prospective bride to participate in Marriage Guidance. Therefore, the KUA emphasizes the process of rafa ‘both’ administrative rafa’ and rafa’ of the future bride and groom’s readiness, with the hope of reducing the number of divorces that occur in Gedangan Sidoarjo.